Language and the African Philosophical Traditions - Kọ́lá Abímbọ́lá (Yoruba Studies Review)
Are there universal principles, categories, or forms of reasoning that apply to all aspects of human experience—irrespective of culture and epoch? Numerous scholars have explored this very question from Africana perspectives: Kwasi Wiredu (1996) explored the philosophical issue of whether there are culturally defined values and concepts; Hallen and Sodipo (1986) examined the question of whether there are unique African indigenous systems of knowledge; Ngũgĩ wa Thiong’o (1994) evaluated the role of colonialism in the language of African literature; Oyerò nkẹ ́ ́ Oyěwumi (1997) argued that “gender” is a Western cultural invention that is foreign to Yorùbá systems of sociation; and Helen Veran (2001) argued that even though science, mathematics, and logic are not culturally relative, “certainty” is nonetheless derived from cultural practices and associations. Building on these and other works, this essay argues that: (i) incommensurability of “worldviews,” “perspectives,” “paradigms,” or “conceptual schemes” springs from deeper, more fundamental cognitive categories of logic that are coded into natural languages; and that (ii) consequently, as long as African reflective reasoning is expressed solely (or predominantly) in European languages, the authenticity of the “African” in African philosophy is questionable.